Sistem fisik - Makna budaya Bali dalam arsitektur Restoran Three Monkeys di Sanur Bali - Sombu, Alwin Suryono; Adityavarman, Ryadi; Talan, John Petrus (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
Bali's Sanur tourism sector is home to many well-known structures with unique, non-Balinese architectural styles. This paper aims to expose the Balinese physical-meaning system found in the Three Monkeys restaurant's architecture in Sanur. The approach is descriptive; first, the